Analisis Mutu Kimia dan Organoleptik Tepache Kulit Nanas (Ananas Comosus L. Merr.) dan Teh Kulit Kopi (Coffea Arabica L.) - Lucia Angelline; Fadjar Kurnia Hartati; Bambang Sigit Sucahyo (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to evaluate the effect of pineapple peels combined with an aqueous infusion of dried coffee peels on the chemical and organoleptic quality of tepache and to determine the best proportion of both materials. The study employed a Completely Randomized Design (CRD) with four treatments and three replications consisting of variations of pineapple peels (F) and coffee peels (K): F1K1 (175 g:25 g), F2K2 (150 g:50 g), F3K3 (125 g:75 g), and F4K4 (100 g:100 g), with a total peel mass of 200 g and 3 days fermentation. Parameters analyzed included pH, total soluble solids, antioxidant activity, and organoleptic properties (color, aroma, and taste) evaluated by 25 panelists using a hedonic scale. The results showed significant effects on total soluble solids, antioxidant activity, and sensory attributes, but not on pH. The best treatment was F1K1, with antioxidant activity of 73.04 ppm and a taste score of 4.4. Tepache has the potential to be developed as a functional beverage based on food waste with added economic value.